2017
DOI: 10.1681/asn.2017020135
|View full text |Cite
|
Sign up to set email alerts
|

BP in Dialysis: Results of a Pilot Study

Abstract: The optimal BP target for patients receiving hemodialysis is unknown. We randomized 126 hypertensive patients on hemodialysis to a standardized predialysis systolic BP of 110-140 mmHg (intensive arm) or 155-165 mmHg (standard arm). The primary objectives were to assess feasibility and safety and inform the design of a full-scale trial. A secondary objective was to assess changes in left ventricular mass. Median follow-up was 365 days. In the standard arm, the 2-week moving average systolic BP did not change si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 58 publications
0
72
0
Order By: Relevance
“…Cardiovascular comorbidity is common in HD patients and further complicates interpretation of blood pressure targets. Extrapolating targets from the general population is unlikely to be helpful and may be harmful, as evidenced by a recent pilot trial designed to achieve lower blood pressures in dialysis patients which reported increased intradialytic hypotensive episodes in patients randomized to achieve lower blood pressure targets . As such it is likely that an individualized approach is required.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular comorbidity is common in HD patients and further complicates interpretation of blood pressure targets. Extrapolating targets from the general population is unlikely to be helpful and may be harmful, as evidenced by a recent pilot trial designed to achieve lower blood pressures in dialysis patients which reported increased intradialytic hypotensive episodes in patients randomized to achieve lower blood pressure targets . As such it is likely that an individualized approach is required.…”
Section: Discussionmentioning
confidence: 99%
“…While observational studies found higher hemoglobin levels to be associated with better survival in patients with CKD, many RCTs, including the Normal Hematocrit Study, showed contradictory findings. This is also true for hypertension targets in patients on dialysis . Thus, the EPISODE study, launched in 2017, may prove to be interesting.…”
Section: Other Issues To Be Addressedmentioning
confidence: 98%
“…The feasibility and safety of intensive BP‐lowering was tested in the Blood Pressure In Dialysis (BID) trial, in which 126 hypertensive hemodialysis patients were randomized to a lower predialysis systolic BP target of 110‐140 mm Hg (intensive arm) vs a higher predialysis systolic BP target of 155‐165 mm Hg (standard arm). Between baseline and month 4, systolic BP fell from 160 to 145 mm Hg in the intensive arm, but remained unchanged in the standard arm.…”
Section: Pharmacological Management Of Hypertensionmentioning
confidence: 99%
“…Although the exact levels at which BP should be targeted remain elusive, meta‐analyses of randomized trials showed that BP‐lowering with the use of antihypertensive therapy improves clinical outcomes, particularly if patients are hypertensive . A recent trial randomizing hemodialysis patients to lower versus higher predialysis BP targets suggested that intensive BP‐lowering in conventional hemodialysis is feasible and does not exacerbate the risk of serious adverse events . Hypertension should be managed first by nonpharmacological strategies aiming to control sodium and volume overload.…”
Section: Introductionmentioning
confidence: 99%